Optimalisasi Media Game Digital dalam Game Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis pada Pelajaran IPA - Fitanti, Sinta Yuni; Prahani, Binar Kurnia; Suryanti, Suryanti; Saphira, Hanandita Veda (JPPS (Jurnal Penelitian Pendidikan Sains), 2025)
Objective: This study has the objective to analyze the implementation of a game-based learning model in improving the critical thinking skills of elementary school students in learning science material on energy sources, focusing on the implementation of learning, the effectiveness of improving critical thinking skills, and student responses. Method: The research method used is quantitative with an experimental design of control group pretest posttest design involving 90 fourth grade students who are divided into three groups: experiment 1 using the digital game "Science Detective", experiment 2 using the board game "Energy Expedition", and the control group with conventional learning. The research instruments included an implementation observation sheet, critical thinking skills test, and learner response questionnaire, with data analyzed using t-test and N-gain calculation. Results: The results showed that the game-based learning model achieved a 96% implementation rate with a very good category. The N-gain in experimental group 1 with high category, experiment 2 with high category, while the control group with medium category. The "Science Detective" game showed consistent improvement in all critical thinking indicators including interpretation, analysis, inference, and evaluation. Learners' responses were very positive. Novelty: The novelty of this research lies in the comprehensive integration of the analysis of implementation, effectiveness, and learner responses to the implementation of game-based learning in the context of elementary school science learning, by developing two different game media for comparison of effectiveness in improving critical thinking skills.